2005
DOI: 10.1007/s10562-005-8007-z
|View full text |Cite
|
Sign up to set email alerts
|

Hβ/HZSM-5 Composite Carrier Supported Catalysts for Olefins Reduction of FCC Gasoline Via Hydroisomerization and Aromatization

Abstract: In order to develop a novel catalyst system that has excellent olefin reduction ability for FCC gasoline without loss in research octane number (RON), different catalysts supported on single-and binary-zeolite carriers consisting of Hb or/and HZSM-5 were prepared and their catalytic performances for FCC gasoline upgrading were assessed in the present investigation. Acidity measurements by pyridine-adsorbed Fourier transformed infrared spectroscopy (FTIR) showed that hydroisomerization and aromatization activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This is because: (1) previous experimental results [12][13][14][15] had confirmed that the n-paraffins and i-paraffins are less active in FCC gasoline hydro-upgrading, as reflected by the great increases in their contents resulting from the olefin conversion; (2) it is known that the adsorption of olefins on bifunctional catalysts is much easier than that of paraffins, and thus the presence of olefins in the feedstock can remarkable restrain the adsorption of paraffins and their subsequent conversion [16,17]; (3) the presence of excess hydrogen also inhibits the paraffin dehydrogenation on non-noble metal sites, namely the first step in the paraffin conversion [18].…”
Section: Lump Selection and The Reaction Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because: (1) previous experimental results [12][13][14][15] had confirmed that the n-paraffins and i-paraffins are less active in FCC gasoline hydro-upgrading, as reflected by the great increases in their contents resulting from the olefin conversion; (2) it is known that the adsorption of olefins on bifunctional catalysts is much easier than that of paraffins, and thus the presence of olefins in the feedstock can remarkable restrain the adsorption of paraffins and their subsequent conversion [16,17]; (3) the presence of excess hydrogen also inhibits the paraffin dehydrogenation on non-noble metal sites, namely the first step in the paraffin conversion [18].…”
Section: Lump Selection and The Reaction Networkmentioning
confidence: 99%
“…Unlike FCC gasoline secondary reactions and FCC gasoline aromatization in the absence of hydrogen, coke formation in FCC gasoline hydro-upgrading can be greatly depressed in the presence of hydrogen [12][13][14]. In view of the very high liquid yield ([98 wt%) of the FCC gasoline hydro-upgrading process [4,12,13], the dry gas and LPG yields are likewise neglectable.…”
Section: Lump Selection and The Reaction Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversions of olefins in FCC gasoline by hydroisomerization and aromatization have been recently investigated by many researchers [59][60][61][62][63]. The loss of octane number from olefin reduction was compensated by the formation of iso-paraffins and aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that by means of operation optimization of FCC units and use of novel olefins reduction FCC catalysts [5][6][7] the olefins content can be decreased to around 35 vol.% [8], which is still much higher than the upper value 18 vol.% as regulated by Europe III vehicle standard of unleaded gasoline. Several selective hydrogenation routes have been proposed and some of them have been put into pilot-scale operations, but none of them enables satisfactory olefins control with acceptable loss in both gasoline research octane number (RON) and yield [8]. Therefore, it is urgent to develop a novel technique that can preserve the octane value while reducing the olefins content of gasoline.…”
Section: Introductionmentioning
confidence: 99%